If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -26 = 3x Reorder the terms: -26 + 5x = 3x Solving -26 + 5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -26 + 5x + -3x = 3x + -3x Combine like terms: 5x + -3x = 2x -26 + 2x = 3x + -3x Combine like terms: 3x + -3x = 0 -26 + 2x = 0 Add '26' to each side of the equation. -26 + 26 + 2x = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 2x = 0 + 26 2x = 0 + 26 Combine like terms: 0 + 26 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 4x+4= | | 63-14x=15-5x+28-7+4 | | 4c+4= | | -x-2y=-2 | | 7x-16-3x=-44 | | y^2-3=5 | | 14+4(x-6)=30 | | y=-1x-4 | | 7x(x+3)=8x+24 | | 2w^2+2w=0 | | 5x+6=-37 | | 4x+36=11x-48 | | 5x^2=13x+17 | | (2x+3)(2x^2-15x+18)=0 | | (4x-8)(8x+2)=0 | | x+6=-21 | | 0.5(3x+6)=1.6-(x+2) | | -3(x-4)-2(x+3)=-5x+6 | | 100-z=65 | | 5,6x=1,176 | | 6x-6=15x-5 | | lnx+ln(2x+1)=4 | | 0.6(4x+8)=1.6-(x+2) | | 10x+2=2x+30 | | -3x^2+9x=1 | | (X-11)(7x-1)=0 | | -3(x-4)-2(x+3)=-5(-1) | | 2t+2=9 | | 6(x+1)/5=3x-1 | | -12=p-7 | | x+y=27 | | 6x-12+4x+2=90 |